Design of single layer interdigital band pass filter with elliptical response - Yuen, Yoon Ming (2005)
The advancement in wireless technology has witnessed the development of many different types of wireless application. Among the more popular application in the recent years are Wireless Local Area Network (WLAN) application and Bluetooth technology. Both applications operate in the microwave region. Microwave filters have become one of the most important components in the whole system. The compactness of interdigital filter makes it a very popular filter where band pass is concern. This thesis focuses on the design of single layer interdigital band pass filter with elliptical response. The chosen frequency of operation is 2.45 GHz, suitable for wireless LAN and Bluetooth applications. MathCAD mathematical software was used to compute all the relevant formulations. In addition, the optimum order of filter was computed to be 4. Investigations on the designed filter were made using the electromagnetic simulation software, Sonnet Suite. The simulated results were satisfactory where the optimum designed filter exhibits the characteristics of an elliptical response band pass filter, albeit large ripples and poor reflections within the passband region. However, improvements can be made in order to achieve a well performed elliptic response bandpass filter